2021
DOI: 10.1038/s41598-021-94602-w
|View full text |Cite
|
Sign up to set email alerts
|

S494 O-glycosylation site on the SARS-CoV-2 RBD affects the virus affinity to ACE2 and its infectivity; a molecular dynamics study

Abstract: SARS-CoV-2 is a strain of Coronavirus family that caused the ongoing pandemic of COVID-19. Several studies showed that the glycosylation of virus spike (S) protein and the Angiotensin-Converting Enzyme 2 (ACE2) receptor on the host cell is critical for the virus infectivity. Molecular Dynamics (MD) simulations were used to explore the role of a novel mutated O-glycosylation site (D494S) on the Receptor Binding Domain (RBD) of S protein. This site was suggested as a key mediator of virus-host interaction. By ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
4
23
1
Order By: Relevance
“…before, the closed-to-open transition of the RBD was analysed by performing PCA on the RBD (residues 330-530) and continuous density distributions for PC1 RBD were finally plotted (red and blue dashed lines in Figure5d). In line with other published data(Casalino et al 2020;Pang et al 2021;Rahnama et al 2021), glycosylation seems to affect the extent of the RBD opening. Even more shifted density distributions were in fact registered for both the S:D614G and [S:A222V + S:D614G] mutants…”
supporting
confidence: 92%
See 1 more Smart Citation
“…before, the closed-to-open transition of the RBD was analysed by performing PCA on the RBD (residues 330-530) and continuous density distributions for PC1 RBD were finally plotted (red and blue dashed lines in Figure5d). In line with other published data(Casalino et al 2020;Pang et al 2021;Rahnama et al 2021), glycosylation seems to affect the extent of the RBD opening. Even more shifted density distributions were in fact registered for both the S:D614G and [S:A222V + S:D614G] mutants…”
supporting
confidence: 92%
“…Other map-to-model quality figures, like FSC-Q (Ramírez-Aportela et al 2021), agreed in this respect (data not shown).Molecular dynamics simulations were also carried out to provide complementary and perhaps less discrete structural details about the subject under study. Considering the importance of glycosylation for the spike dynamics(Casalino et al 2020;Pang et al 2021, Rahnama et al 2021, MD trajectories were collected starting from our cryo-EM structures as well as from previously reported structural models with and without glycosylation.Results from PCA relative to the RBD closed-to-open transition pointed out the preference for a more open RBD for the [S:A222V + S:D614G] mutant, with glycosylation additionally enhancing the openness of the open RBD, inagreement with a recent study(Pang et al 2021). Furthermore, dynamic network analysis allowed us to go deeper into the allosteric nature of the possible changes induced by the S:A222V mutation.…”
mentioning
confidence: 99%
“…Attachment of the O-glycans to S494 can increase the binding affinity of virus to ACE2. 354 The predicted O-linked glycosylation residues at S673, T678 and S686 are near the RRAR position, 36 , 337 implying their potential functions in virus penetration. 332 , 337 , 359…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the levels of O-glycosylation at T323 and S325 are relative higher, while the glycosylation of other O-glycosites are in low occupancy. 40 , 63 , 70 , 329 , 332 , 336 338 The O-glycans identified on O-glycosites of S protein and RBD from human cells as well as deduced O-glycan structures were summarized 70 , 80 , 328 , 332 , 336 , 338 , 340 – 342 , 354 – 357 (Table 2 , Table 3 ). O-linked glycans such as Core-1, 336 disialylated Core-1, 332 Core-2, 328 mucin-type, 339 and sialylated mucin type are reported on the recombinant S protein.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the size of O-glycan in the glycosylated S protein appears as a factor that modulates the affinity of virus-receptor interaction. An increase in the size of O-glycan in the S protein enhances its interaction with the ACE2 receptor [80]. In addition, it has been suggested that to enter human cells, SARS-CoV2 requires furin protease [81].…”
Section: Antigenic Changes In Sars-cov-2mentioning
confidence: 99%